(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the impact of Human Resource Management (HRM) practices, represented by the dimensions of human resource planning, recruitment and selection, training and development, compensation and incentives, and performance appraisal, on Organizational Change Management (OCM), represented by the dimensions of organizational culture, organizational structure, and technology, in private hospitals located in Sana’a Capital Municipality, Yemen. To achieve the study objectives, the descriptive-analytical approach was employed. The study population consisted of employees working in private hospitals in Sana’a Capital Municipality, totaling 2,908 employees. A simple random sample of 341 respondents was selected. A structured questionnaire was used as the primary instrument for data collection. The findings revealed that HRM practices, including human resource planning, recruitment and selection, training and development, compensation and incentives, and performance appraisal, have a significant impact on organizational change management in private hospitals in Sana’a Capital Municipality. The results also indicated that both the level of implementation of HRM practices and the level of organizational change management were high. Based on these findings, the study recommends implementing an objective, transparent, and clearly defined performance appraisal system based on well-established Key Performance Indicators (KPIs). It further recommends that HR managers in private hospitals place greater emphasis on modern specialized training programs to enhance employees’ technical and supervisory competencies. Additionally, the study emphasizes the importance of developing compensation and incentive systems and linking them to performance and productivity standards to promote fairness, motivation, and innovation. Greater attention should also be given to human resource planning, recruitment, and selection processes to support organizational effectiveness and successful change initiatives.